A new species of Neohylomys (Eulipotyphla: Galericidae) from northern Vietnam - Bannikova, Anna A.; Lebedev, Vladimir S.; Gorchkhanov, Dzhabrail; Fei, Li; Dung, Dinh The; Hai, Bui Tuan; Kruskop, Sergei V.; Rozhnov, Viatcheslav V.; Abramov, Alexei V. (Zootaxa, 2024)
A new species of gymnure of the genus Neohylomys is described from northern Vietnam based on morphological and molecular differences. The species Neohylomys vietnamensis sp. nov. differs from the closely related species N. hainanensis from Hainan Island, China, previously the only species of the genus Neohylomys, by morphological and morphometric traits and by the mitochondrial cytb (8% of divergence) and nuclear BRCA1 genes. To date, the new species is known to exist only in northern Vietnam.